MARKET ATTRACTION AND CAPABILITY FACTORS IN IMPROVING MARKETING PERFORMANCE THROUGH STRATEGIC DEVELOPMENT - Rahayu Kusumadewi (Fakultas Ekonomi dan Bisnis Universitas Padjadjaran, 2020)
Private universities have high competition and demand to show their quality and reliable competitiveness. This research aims to analyze the attraction factor of private universities and their capabilities in supporting the development of marketing strategy and performance. This research applied a quantitative model with descriptive and verification analysis, and the used analytical tool is the SEM analysis model. The sampling technique is cluster proportional random sampling covering respondents from the stakeholders of the private university in West Java. The research findings prove that the attraction and capability factors have a significant influence on strategy, and the strategy has an effect on marketing performance, and the development of strategic planning as a strategic guideline in achieving the organization’s vision and mission, which in turn can realize superior marketing performance. Moreover, this study reveals that the capacity factor has an essential influence on private universities, in particular, when paying attention to the dynamic aspects of technology and information development. Technology and information have a very significant role in realizing the superior quality of universities and can build their perceptions in the community. Another important finding is that the capacity factor has a stronger effect than the attraction factor. That is, the capability factors consisting of resources, management systems, financial strength, infrastructure support, and information technology ownership have a very strong influence in determining marketing performance.